Anti-inflammatory effects of Punica granatum Linne in vitro and in vivo - Lee, Chia-Jung; Chen, Lih-Geeng; Liang, Wen-Li; Wang, Ching-Chiung (Food chemistry, 2010)
Inflammation can cause various physical dysfunctions. Punica granatum Linne (pomegranate), a high phenolic content fruit, is widely used as an antipyretic analgesic in Chinese culture. Pomegranate has shown potential nitric oxide (NO) inhibition in LPS-induced RAW 264.7 macrophage cells. Moreover, pomegranate (100 mg/kg) significantly decreased carrageenan-induced mice paw edema for 1, 3, 4, and 5 h. Therefore, column chromatography combined with in vitro bioassay-guided fractionation was used to isolate the active anti-inflammatory components from the pomegranate. Punicalagin ( 1), punicalin ( 2), strictinin A ( 3), and granatin B ( 4) were obtained with yields of 0.093%, 0.015%, 0.003%, and 0.013%, respectively. All these hydrolysable tannins inhibited NO production and iNOS expression in RAW 264.7 cells. Among them, 4 showed the strongest iNOS and COX-2 inhibitory effects, and exhibited these effects in the inhibition of paw swelling and the PGE 2 level in carrageenan-induced mice. Taken together, we suggest that 4 could be used as a standard marker for the anti-inflammatory effect of pomegranate.